Assessment of “Specific Safety” Index of the Live Tularemia Vaccine - I. S. Barulina; L. V. Sayapina; N. P. Baidalova; I. I. Khoreva; I. S. Mescheryakova; M. I. Kormilitsyna; S. A. Korovkin (Проблемы особо опасных инфекций, 2009)
Analyzed were the results of specific safety control of the live tularemia dry vaccine used for tularemia prophylaxis. During the period of 1997-2006 this index was shown to be unstable. Specific safety of the vaccine is one of the main parameters of its quality, and in cases it does not meet the requirements of the normative documentation (ND) the vaccine is rejected during the control. It was proposed to introduce amendments in ND and to use for vaccine control standard animals, the conditions of their keeping being strictly observed.